Successful recanalization of disconnected donor and recipient ducts due to severe anastomotic biliary stricture after liver transplantation using the rendezvous technique: novel solution to an old problem - Singh, Harnoor; Mehendiratta, Vaibhav; Richardson, Elizabeth; Collins, Daniel; Serrano, Oscar K. (International Surgery Journal, 2026)
Biliary strictures are a common adverse event (AE) following liver transplantation (LT) and can be challenging to manage when severe. Standard treatment with endoscopic retrograde cholangiopancreatography (ERCP) and stenting may fail and require alternative approaches. A 27-year-old woman developed a severe biliary stricture six months post-LT for acetaminophen-induced acute liver failure. The patient’s clinical course was complicated by cholangitis. ERCP and percutaneous transhepatic cholangiography (PTC) showed complete obstruction at the anastomosis level, resulting in disconnected donor and recipient ducts. A combined endoscopic-percutaneous rendezvous procedure successfully achieved biliary recanalization and stent placement, relieving obstruction and avoiding surgical revision or re-transplantation. The rendezvous technique is a safe, effective, and minimally invasive option for complex post-transplant biliary strictures when conventional methods are unsuccessful.